Premarital and Extramarital Relationships: A Study of A Selected Slum in Dhaka, Bangladesh - Md Muniruzzaman; Md. Roknuzzaman Siddiky; Shahanaz Akter; Israt Eshita Haque (Universitas Djuanda, 2023)
Premarital and extramarital relationships among the slum dwellers in Dhaka city have become a matter growing concern. However, it has not been yet spotlighted in empirical research. As such, the main purpose of the study was to identify the causes and consequences of premarital and extramarital relationships. The study was a qualitative study where multiple case-study design was employed. Primary data were collected via in-depth interviews from ten participants by using snowball sampling. Moreover, three key informants were interviewed for further supportive information. The study shows that poor social environment and living conditions, learning unethical sexual practice from close friends, falsehood promise for marriage, and uncontrolled sexual desire are the major causes of premarital and extramarital relationship among the slum dwellers. The study also reveals that unsafe and unprotected sexual intercourse, unintended pregnancies and induced abortions, domestic violence and divorce, and the risk of spreading STDs and STIs are major potential consequences of premarital and extramarital relationships among the slum dwellers and thus the issues are a great threat to social and environmental well-being. The study suggests that both government and non-government organizations should undertake proper policy measures and programs such as propagation of health awareness programs, especially on HIV/AIDS and STDS, provision of civic amenities, enforcement of laws, and development of moral values to minimize premarital and extramarital relationships among slum dwellers